Whose Book Is it Anyway?: A View from Elsewhere on Publishing, Copyright and Creativity - Jefferies, Janis (Editor) (Open Book Publishers, 2019)
Whose Book is it Anyway? is a provocative collection of essays that opens out the copyright debate to questions of open access, ethics, and creativity. It includes views - such as artist's perspectives, writer's perspectives, feminist, and international perspectives - that are too often marginalized or elided altogether.